Learning to Implement Teaching Games for Understanding During Teaching Practice: 學習在實習期間實踐領會教學法 - CRUZ, Alberto; LI , Chung; KAM, Kevin Wai Keung (Asian Journal of Physical Education & Recreation, 2012)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purposes of this study were to examine the process of learning to teach TGfU and the factors that influence student teachers to implement this approach during the teaching practice. 23 secondary student teachers who intended to try the approach in the teaching practices were purposely invited to take part in the study. Passive participant observation, formal and informal interviews, journal writing and document analysis were used to collect qualitative data. Data were organized and analyzed through inductive analysis and constant comparison. The participants equipped the knowledge of application of the TGfU through various learning channels: Trial teaching, observation of peer teaching and discussion among colleagues. Post-lesson reflections also helped to refine their practices. They spent much time in lessons preparation. They adopted “start and end with a game” lesson format and used facilitated questions between the game activities. Students, teaching experience, preparation, class management, school facilities and support were major factors influencing the implementation of TGfU. They emphasized the importance of the experiences of implementation and the post-lesson reflective process within the learning to teach process. Findings of the study hold implications for the practice of physical education teacher educators with respect to the learning to teach TGfU process. 本研究目的是探討學習教授領會教學法及影響實習老師於實習時實踐領會教學法的因素。二十三位實習老師參與是次研究。透過被動參與式觀察、正式及非正式訪問、老師反思日誌及文件分析等方法收集數據。然後以持續比較法分析資料。結果顯示實習老師透過不同學習模式掌握應用領會教學法知識。影響實習老師實踐領會教學法因素包括學生、教學經驗、準備、課堂管理、設施及支援。此等結果給予體育師資工作者培訓領會教學法多方面啟示。